Cilia - Marshall, Wallace F. (Methods in enzymology, 2013)
This new volume of Methods in Enzymology continues the legacy of this premier serial with quality chapters authored by leaders in the field. This volume covers cilia and includes chapters on such topics as methods for studying ciliary polarity in Xenopus, analysis of signaling pathways in mammalian spermatozoa, and biochemical and physiological analysis of axonemal dyneins. Continues the legacy of this premier serial with quality chapters authored by leaders in the field Covers cilia Contains chapters on such topics as methods for studying ciliary pol.